Liquidity Impact of Novel Market Surveillance Measures—An Evidence from India - Inamdar, Mohd Merajuddin; Chari, Latha (FIIB business review, 2023)
Stock price manipulation can be defined as trading behaviour that distorts stock prices with the intent of personal gains. Securities market regulators around the world undertake market surveillance to prevent market manipulation protect investors and ensure market integrity. The Securities Exchange Board of India along with stock exchanges has implemented a novel additional surveillance measure (ASM) which tracks stocks on a daily basis for abnormal price and volume activity accompanied by the participation of market-dominating investors in trading activity. Stocks that breach predefined limits of the above parameters are categorized as ASM category and subject to overall additional margins and selective additional margins for the dominating investor. There are mainly two types of ASM, Long term additional surveillance measures (LTASM) and short-term additional surveillance measures (STASM). STASM consider a shorter duration time (5/15 days) for share price observation LTASM considers a longer duration (1 month/1 year) for screening of the stock for surveillance measures as per ASM criteria. This study is based on STASM. The mechanism, on the one hand, is expected to deter manipulators and on the other, warn investors about suspicious activity in the stock, which is not supported by fundamentals. This article analyses the impact of surveillance actions on a price return and liquidity. The article also looks at the degree of speculative activity surrounding the event. This study used regression analysis for impact assessment. The study results show that the prices of the stock stabilize after inclusion and there is an overall fall in liquidity post-inclusion. However, the liquidity impact is different for stocks with positive abnormal returns as compared to those with negative abnormal returns. The result of the study gives insight into the effectiveness of STASM which will be useful for regulators and investors to prevent market manipulations.